Temporary Fecal Diversion in the Management of Colorectal and Perianal Crohn’s Disease - Rudolf Mennigen; Britta Heptner; Norbert Senninger; Emile Rijcken (Gastroenterology Research and Practice)
Aim. To evaluate the results of temporary fecal diversion in colorectal and perianal Crohn’s disease. Method. We retrospectively identified 29 consecutive patients (14 females, 15 males; median age: 30.0 years, range: 18–76) undergoing temporary fecal diversion for colorectal (n=14), ileal (n=4), and/or perianal Crohn’s disease (n=22). Follow-up was in median 33.0 (3–103) months. Response to fecal diversion, rate of stoma reversal, and relapse rate after stoma reversal were recorded. Results. The response to temporary fecal diversion was complete remission in 4/29 (13.8%), partial remission in 12/29 (41.4%), no change in 7/29 (24.1%), and progress in 6/29 (20.7%). Stoma reversal was performed in 19 out of 25 patients (76%) available for follow-up. Of these, the majority (15/19, 78.9%) needed further surgical therapies for a relapse of the same pathology previously leading to temporary fecal diversion, including colorectal resections (10/19, 52.6%) and creation of a definitive stoma (7/19, 36.8%). At the end of follow-up, only 4/25 patients (16%) had a stable course without the need for further definitive surgery. Conclusion. Temporary fecal diversion can induce remission in otherwise refractory colorectal or perianal Crohn’s disease, but the chance of enduring remission after stoma reversal is low.